2010
DOI: 10.2478/s11535-010-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic patterns of malaria incidence in Burundi

Abstract: Best available descriptions of malaria incidence and mortality dynamics are important to improve and evaluate the implementation of programs to monitor (e.g., remote sensing) and control disease, especially in endemic zones. High-frequency (e.g., semi-annual and seasonal) cycles in malaria incidence have been observed in various countries and they coincide with cycles in the natural environment (e.g., temperature, heliogeophysical activity, etc.). However, neither trend nor cyclical oscillations beyond a 6-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In terms of vegetation and malaria cases, the present study identified significant lags of 3–23 weeks while in Burundi and Ethiopia, 8 and 12 weeks were significantly correlated to vegetation and malaria [ 27 , 31 ]. As demonstrated in previous studies, malaria transmission and mosquito abundance can be influenced by vegetation cover through provision of an outdoor resting place for the vector [ 14 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In terms of vegetation and malaria cases, the present study identified significant lags of 3–23 weeks while in Burundi and Ethiopia, 8 and 12 weeks were significantly correlated to vegetation and malaria [ 27 , 31 ]. As demonstrated in previous studies, malaria transmission and mosquito abundance can be influenced by vegetation cover through provision of an outdoor resting place for the vector [ 14 ].…”
Section: Discussionmentioning
confidence: 95%
“…More recently however, significant associations were seen at lags starting from 7 and 13 weeks in Kenya [ 26 ]. In the highlands of Burundi, a lag of 4 weeks was significant between temperature and malaria [ 27 ], while lags of 4 and 8 weeks were significant for an area of unstable malaria transmission in Rwanda [ 23 ]. Temperature has been documented to affect survival and growth of both the vector and the parasite in the vector [ 28 – 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different statistical methods for time-series analyses and modelling were used, according to a previously described algorithm used to detect cyclicity in similar monthly malaria time-series [18]. Initially, descriptive statistics with linear and nonlinear regression modelling over time were applied (Figs 1–3).…”
Section: Methodsmentioning
confidence: 99%
“…change over time of the revealed cyclicities ( Figs 6, 7). In particular, PRA was successfully applied earlier in studies on helioepidemiology of various types of cancer and infectious diseases as described previously in more detail elsewhere [13,[18][19][20][21]. A range (spectrum) of the linear coefficients of correlation R was constructed against each of the tested periods T (months) representing the so-called 'periodogram ' (e.g.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation